Komparasi Perangkat Ajar Dalam Pembelajaran IPS Di SD Rajaprajanugroh 39 Thailand Selatan Dan SDN Suryakencana CBM Kota Sukabumi - Shafa Aulia Nissa; Iis Nurasiah; Rifky Aditya Ramadhan (Jayapangus Press, 2026)
Teaching tools are a crucial component for successful learning. This study aims to compares teaching materials for social studies in two elementary schools in different countries, namely Rajaprajanugroh 39 Elementary School in Southern Thailand and Suryakencana CBM Elementary School in Sukabumi, Indonesia. This study aims to analyze the social studies learning materials used in both countries and identify the similarities and differences in the social studies learning materials in both schools. This research is a qualitative study with a descriptive approach. Data collection techniques were conducted through documentary studies of teaching modules, observation of the learning process, and in-depth interviews with educators at both schools. The research results show that most striking differences in the content and completeness of the administrative components within the learning modules. The social studies teaching modules in Southern Thailand and Indonesia each have their own advantages, influenced by curriculum policies, cultural contexts, and student needs. The teaching modules at SDN Suryakencana CBM have more detailed components, including specific mentoring plans such as remedial and enrichment sessions, as well as initial assessments to determine student readiness. Meanwhile, the teaching modules at SD Rajaprajanugroh 39 are simple and focus on classroom activity steps and post-teaching evaluations. Although the content and components are different, both schools have strong similarities in using active learning models, such as inviting students to solve problems together and creat real works. These findings provide insight into the advantages of teaching modules from both countries that can be adapted to improve the quality of social studies learning tools at the elementary school level.